Communications: Characteristics of Inner-City Students and the Implications for Management (Administrative) Education - Jones, Donald (Academy of Management Journal, 1971)
The article reports the author's opinions regarding the accessibility of business education in the U.S. The author focuses on the availability of business education courses to residents of inner-city ghettos. It is suggested that business teachers and university administrators take socioeconomic factors into consideration when planning a business curriculum for minority groups living in the inner-city.